Review of Bio-Plastic Products Based on Fruit and Vegetable Waste - Hanif Ardhiansyah; Maharani Kusumaningrum; Ria Wulansarie; Nadya Alfa Cahaya Imani (Jurnal Inovasi Teknik Kimia, 2024)
In the realm of sustainable materials, bio-plastics derived from fruit and vegetable waste have emerged as eco-friendly alternatives to traditional plastics. This mini review explores the promising landscape of bio-plastic products originating from agricultural by-products. Fruit and vegetable waste, abundant in nature, is being ingeniously repurposed to create biodegradable and compostable plastics, addressing the environmental concerns associated with conventional plastics. Researchers and innovators have harnessed the inherent properties of organic waste, utilizing its fibrous and polymeric components to develop bio-based polymers. These bio-plastics showcase commendable mechanical and thermal properties, making them viable contenders for various applications. From packaging materials to disposable cutlery, the versatility of fruit and vegetable waste-based bio-plastics is expanding. The review delves into the manufacturing processes, emphasizing the importance of sustainable practices in the production of these materials. Additionally, it sheds light on the environmental impact, decomposition rates, and potential challenges associated with the adoption of bio-plastic products. As the world seeks greener alternatives, the utilization of fruit and vegetable waste in bio-plastic production not only mitigates pollution but also promotes a circular economy by repurposing agricultural leftovers. This exploration underscores the transformative potential of harnessing nature's surplus for a more sustainable and responsible future.